Chromosome-level analysis of the Colletotrichum graminicola genome reveals the unique characteristics of core and minichromosomes - Becerra, Sioly; Baroncelli, Riccardo; Boufleur, Thaís R.; Sukno, Serenella A.; Thon, Michael R. (Frontiers in Microbiology, 2023)
The fungal pathogen Colletotrichum graminicola causes anthracnose of maize (Zea mays) and is responsible for significant yield losses worldwide. The genome of C. graminicola was sequenced in 2012 using Sanger sequencing, 454 pyrosequencing and an optical map to obtain an assembly of 13 pseudochromosomes. We resequenced the genome using a combination of short-read (Illumina) and long-read (PacBio) technologies to obtain a chromosome level assembly. The new version of the genome sequence has 13 chromosomes with a total length of 57.43 Mb. We detected 66 (23.62 Mb) structural rearrangements in the new assembly with respect to the previous version, consisting of 61 (21.98 Mb) translocations, 1 (1.41 Mb) inversions, and 4 (221 Kb) duplications. We annotated the genome and obtained 15,118 predicted genes, 3,614 new gene models compared to the previous version of the assembly. We show that 25.88% of the new assembly is composed of repetitive DNA elements (13.68% more than the previous assembly version), which are mostly found in gene-sparse regions. We describe genomic compartmentalization consisting of repeat-rich and gene-poor regions vs repeat-poor and gene-rich regions. 1,140 secreted proteins were found mainly in repeat-rich regions. We also found that approximately 75% of the three smallest chromosomes (minichromosomes, between 730 and 551 Kb) are strongly affected by repeat-induced point mutation (RIP) compared with the 28% of the larger chromosomes. The gene content of the minichromosomes (MCs) comprises 121 genes of which 83.6% are hypothetical proteins with no predicted function, while the mean percentage of Chr1-Chr10 is 36.5%. No predicted secreted proteins are present in the MCs. Interestingly, only 2% of the genes in Chr11 have homologs in other strains of C. graminicola while Chr12 and 13 have 58% and 57% respectively, raising the question as to whether Chrs12 and 13 are dispensable. The core chromosomes (Chr1-Chr10) are very different with respect to the MCs (Chr11-Chr13) in the content and the sequence features. We hypothesize that the higher density of repetitive elements and RIPs in the MCs may be linked to the adaptation and/or host co-evolution of this pathogenic fungus.